“I Get Blank When I Start Writing”: Analysis of EFL Student’s Anxiety In Writing Descriptive Text - Puspitasari, Yuyun; Quthny, Abu Yazid Adnan; Hamdani, Beny (Journey: Journal of English Language and Pedagogy, 2024)
In various educational worlds, of course, we learn foreign languages, one of which is English. English is challenging and can cause anxiety, one of which is in writing. English as a Foreign Language (EFL) learners often face many challenges when it comes to developing their writing skills. The recent research aims to discuss EFL students’ anxiety in writing descriptive text. This study used narrative inquiry. A narrative inquiry explore the experiences and feelings of an EFL students’ writing anxiety. The research participants are two students. These two students were taken from 1 Senior high school student and one was taken from Junior high school. Data collection uses semi-structured interview with 45 minutes. The interviews were held at a private Islamic boarding school in Probolinggo East Java. Data Analysis uses thematic Analysis. The results of this study reveal that students' writing anxiety level is still relatively high, therefore, teacher motivation and guidance to students must be increased so that students can deal with or evaluate writing anxiety experienced by students. Finally, in learning English as a second language (ESL), it is important for students to have adequate vocabulary knowledge so that they are not confused and anxious to write English texts.